Menedżerowie i mafiosi: etyka motywowania w autobiografich "self-made manów" - Szukała, Michał (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper is an attempt to verify the assumptions of the motivation-hygiene theory byFrederick Herzberg in the context of the values and practices of leading managers ofthe U.S. economy. The two-factor theory is a part of every synthesis of managementscience, although its assumptions raise serious controversies. The subject matter of theanalysis is the biographies of the most prominent managers, such as Henry Ford, LeeIacocca, Walter P. Chrysler and Jordan Belfort (known as the ‘Wolf of Wall Street’).The basic aim of the analysis is to check their biographical story in the context of theirmotivation issues. The selection of characters has been imposed by the feature of beingself-made men.It seems that their descriptions of how to motivate employees may be interpretedas a specific manifestation of values important to them in the perception of economiclife and the interpersonal relations in structures of corporations functioning in differentmarket circumstances. The choice of source materials from different historical momentsand different economic spheres shows a conversion of values and goals in the Americaneconomy. One of the results of the analysis is the observation that Herzberg’s theorydoes not reflect the multiplicity of factors that may have a significant impact on the motivationof employees to perform their duties as well as possible. One of the aims of thediscussion is to indicate the unusual source material, considered by many researchers asanecdotal, as potentially attractive for analyses in the field of the management sciences.